1142. Plasma with high titers of anti-SARS-Cov2 antibodies improves outcome of COVID-19 in patients with hematological malignancy and cancer in a randomized controlled trial. (15th December 2022) - Denkinger, Claudia M; Janssen, Maike; Schäkel, Ulrike; Gall, Julia; Leo, Albrecht; Stelmach, Patrick; Weber, Stefan F; Krisam, Johannes; Baumann, Lukas; Stermann, Jacek; Merle, Uta; Weigand, Markus; et al.
Abstract: Background: Patients with hematological malignancy or other cancers as well as immunosuppression bear a high risk for severe COVID-19. Monoclonal antibodies (mAb) are efficient at early stages of the disease but may lose potency with new variants. Trials on plasma from convalescent donors in unselected patients have not shown clinical benefit. No randomized trials focussing on patients with underlying disease have been published. Methods: We conducted an open-label, multicenter, randomized controlled trial to evaluate efficacy of plasma (CVP - convalescent or after vaccination) in patients with COVID-19 at high risk for adverse outcome in Germany. We assessed the effect of high-titer CVP (2 units from different donors, 238-337 ml each, on subsequent days). Patients with hematological or other malignancy (group 1), immunosuppression (group 2), age >50 and ≤75 years and lymphopenia and/or high D-dimers (group 3) or age >75 years (group 4) who were hospitalized with confirmed SARS-CoV-2 infection and with an oxygen saturation ≤94% were included. Primary outcome measure was time to clinical improvement on a seven-point ordinal scale, secondary outcome was mortality (Janssen et al. Trials 2020 Oct 6;21(1):828). Results: Overall, 133 patients were randomized, 68 received CVP with an additional 10 patients as a crossover on day 10. Median age (range) was 68 years (39-95) in the CVP group and 70 (38-90) in controls. For the entire cohort, no significant difference was seen in time to improvement (median days: CVP 12.5 vs. control 18; HR 1.24 (95% confidence interval (CI) 0.83-1.85), p=0.29). Subgroup analysis (group 1+2) revealed shortened time to improvement (median days CVP 13 vs. control 32; HR 2.03 (95%CI 1.17-3.6), p=0.01) and mortality was reduced (mortality CVP n=6 (18%) vs. control n=10 (29%). No significant differences in time to improvement were observed in group 3 or 4 (HR 0.72 (95%CI 0.41-1.28), p=0.26). No relevant adverse events were observed. Conclusion: CVP improves time to clinical improvement and mortality for COVID-19 patients with underlying hematological disease/cancer or other reasons of impaired immune response. Even with new variants, high-titer CVP may offer a widely available and inexpensive therapy option in high-risk groups. Funding: BMBF FKZ 01KI20152; EudraCT 2020-001632-10. Disclosures: Uta Merle, MD, Gilead: Sponsored congress travel and accommodation Markus Weigand, MD, Bbraun: Speakers fee/ad boards fee|Biotest: Speakers fee/ad boards fee|Eumedica: Speakers fee/ad boards fee|Gilead: Speakers fee/ad boards fee|MSD: Speakers fee/ad boards fee|Pfizer: Speakers fee/ad boards fee|Shionogi: Speakers fee/ad boards fee|SOBI: Speakers fee/ad boards fee Martin Bornhäuser, MD, Alexion: Honoraria|Jazz Pharmaceuticals: Honoraria|MSD: Honoraria|Novartis: Honoraria Nael Alakel, MD, Amgen: personal fee, travel grant|Gilead: personal fee, travel grant|MSD Sharp and Dohme GmbH: personal fee, travel grant|Pfizer: personal fee, travel grant Timo Wolf, MD, Gilead Sciences: Lecture fee, travel grant|Janssen Pharmaceuticals: Lecture fee, travel grant|Merck Sharp Dome: Lecture fee, travel grant Maria Vehreschild, Prof. Dr., 3M: speaker fee|Astellas: Advisor/Consultant|Astellas: speaker fee|biologische heilmittel heel gmbh: Grant/Research Support|BioNtech: Grant/Research Support|EUMEDICA: Advisor/Consultant|Farmak International Holding: Advisor/Consultant|Ferring: Advisor/Consultant|Ferring: Speaker fee|Gilead Sciences: Advisor/Consultant|Immunic AG: Advisor/Consultant|MaaT: Advisor/Consultant|Merck: Advisor/Consultant|Merck: speaker fee|MSD: Advisor/Consultant|MSD: Grant/Research Support|MSD: speaker fees|Pfizer: speaker fee|Roche Molecular Systems: Grant/Research Support|Roche Molecular Systems: speaker fees|SocraRTec R&D GmbH: Advisor/Consultant|Takeda California: Grant/Research Support Hanns-Martin Lorenz, MD, Abbvie: Advisor/Consultant|Abbvie: Honoraria|Actelion: Advisor/Consultant|Actelion: Honoraria|Alexion: Advisor/Consultant|Alexion: Honoraria|Amgen: Advisor/Consultant|Amgen: Grant/Research Support|Astra Zeneca: Advisor/Consultant|Astra Zeneca: Honoraria|Baxter: Advisor/Consultant|Baxter: Advisor/Consultant|Baxter: Honoraria|Baxter: Honoraria|Bayer Vital: Advisor/Consultant|Bayer Vital: Honoraria|Biogen: Advisor/Consultant|Biogen: Honoraria|BMS: Advisor/Consultant|BMS: Honoraria|Boehringer Ingelheim: Advisor/Consultant|Boehringer Ingelheim: Honoraria|Celgene: Advisor/Consultant|Celgene: Honoraria|Fresenius: Advisor/Consultant|Fresenius: Honoraria|Genzyme: Advisor/Consultant|Genzyme: Honoraria|Gilead/Galapagos: Advisor/Consultant|Gilead/Galapagos: Honoraria|GSK: Advisor/Consultant|GSK: Honoraria|Hexal: Advisor/Consultant|Hexal: Honoraria|Janssen-Cilag: Advisor/Consultant|Janssen-Cilag: Honoraria|Lilly: Advisor/Consultant|Lilly: Honoraria|Medac: Advisor/Consultant|Medac: Honoraria|MSD: Advisor/Consultant|MSD: Honoraria|Mundipharm: Advisor/Consultant|Mundipharm: Honoraria|Mylan: Advisor/Consultant|Mylan: Honoraria|Novartis: Advisor/Consultant|Novartis: Honoraria|octapharm: Advisor/Consultant|octapharm: Honoraria|Pfizer: Advisor/Consultant|Pfizer: Honoraria|Roche/Chugai: Advisor/Consultant|Roche/Chugai: Honoraria|Sandoz: Advisor/Consultant|Sandoz: Honoraria|Sanofi: Advisor/Consultant|Sanofi: Honoraria|Shire: Advisor/Consultant|Shire: Honoraria|SOBI: Advisor/Consultant|SOBI: Honoraria|Thermo Fisher: Advisor/Consultant|Thermo Fisher: Honoraria|UCB: Advisor/Consultant|UCB: Honoraria.